Influencia del uso de Instrumentos Musicales de Percusión elaborados con material reciclable para mejorar la atención en los niños de tres años de la I. E. N° 209 “Santa Ana”, de la ciudad de Trujillo, en el año 2016 - Haro Blas, Cindy Maylin (2017)
The present research aims to raise awareness of the influence of the use of percussion musical instruments made from recyclable material._x000D_ The research is applied with quasi-experimental design, with experimental group and control group with pretest and posttest._x000D_ The experimental group consisted of 20 children, 3 years old, who participated in the sessions scheduled to improve their care and learning, and this was done in the facilities of the I.E. N ° 209 "Santa Ana"._x000D_ The results of the pretest show that the children had a low level of attention. After applying the sessions using the percussion musical instruments, and making use of playful and educational strategies, the children of the experimental group were significantly increased their attention.